Academic Language as a Predictor of Reading Comprehension in Monolingual Spanish‐Speaking Readers: Evidence From Chilean Early Adolescents. Issue 2 (7th June 2017) - Meneses, Alejandra; Uccelli, Paola; Santelices, María Verónica; Ruiz, Marcela; Acevedo, Daniela; Figueroa, Javiera
Abstract: Although literacy achievement has improved in Chile, adolescents' underperformance in reading comprehension is still a serious concern. In English, core academic‐language skills (CALS) have been found to significantly predict reading comprehension, even controlling for academic vocabulary knowledge. CALS are high‐utility language skills that support reading comprehension across school content areas. Guided by an operational definition of Spanish CALS (S‐CALS), three goals drove this study: to develop two psychometrically reliable tests, the S‐CALS Instrument and the Spanish Academic Vocabulary (S‐AVoc) Test; to explore the dimensionality of core academic‐language proficiencies, as measured by these two tests; and to examine the contribution of core academic‐language proficiencies to reading comprehension. A cross‐sectional sample of 810 Chilean students (grades 4–8) participated in four assessments that measured standardized reading comprehension, word‐reading fluency, Spanish academic vocabulary, and S‐CALS. Using classical test theory and item response theory analyses, results yielded robust reliability evidence for both instruments. Consistent with prior research, S‐CALS and academic vocabulary scores displayed upward trends in higher grades yet considerable within‐grade variability. Confirmatory factor analysis revealed that S‐CALS and S‐AVoc were best conceptualized as part of a higher order construct, the Spanish core academic‐language and vocabulary skills (S‐CALVS). The aggregated S‐CALVS scores predicted reading comprehension, beyond the contribution of grade, school factors, and word‐reading fluency. This study advances our scientific understanding of CALS as relevant for adolescent literacy beyond the English language. The high‐utility school‐relevant language and vocabulary skills offer promising tools to inform and evaluate innovative reading comprehension interventions for Spanish‐speaking adolescents.